2003
DOI: 10.1211/002235702423
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro evaluation of bioadhesion in particulate systems and possible improvement using interactive mixtures

Abstract: There is much interest in predicting the properties of pharmaceutical dosage forms from the properties of the raw materials they contain. Achieving this with reasonable accuracy would aid the faster development and manufacture of dosage forms. A variety of approaches to prediction or correlation of properties are reviewed. These approaches have variable accuracy, with no single technique yet able to provide an accurate prediction of the overall properties of the dosage form. However, there have been some succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Camphor and menthol were chosen as sublimable materials, to induce pores into the compressed tablets, as they have the ability to sublimate (i.e., transit from solid phase directly to vapor phase without passing through an intermediate liquid phase). Kollidon CL was included in the formulations as a bioadhesive component in order to increase the contact time of vinpocetine at the sublingual mucosa, thereby reduce the potential intra/inter-individual variability resulting from swallowing the drug [13, 25]. Nevertheless, it is reported that Kollidon CL does not interfere with the rapid disintegration of the tablets [26].…”
Section: Resultsmentioning
confidence: 99%
“…Camphor and menthol were chosen as sublimable materials, to induce pores into the compressed tablets, as they have the ability to sublimate (i.e., transit from solid phase directly to vapor phase without passing through an intermediate liquid phase). Kollidon CL was included in the formulations as a bioadhesive component in order to increase the contact time of vinpocetine at the sublingual mucosa, thereby reduce the potential intra/inter-individual variability resulting from swallowing the drug [13, 25]. Nevertheless, it is reported that Kollidon CL does not interfere with the rapid disintegration of the tablets [26].…”
Section: Resultsmentioning
confidence: 99%
“…Another potential benefit to using the disintegrant Ac-DiSol is the mucoadhesivity of this excipient [20]. Although very few studies have been made using mucoadhesive rectal formulations [21], it has been suggested that the addition of mucoadhesive polymers to conventional solid suppositories can increase the bioavailability of certain drugs, particularly those that are sensitive to first passage metabolism [22].…”
Section: Discussion Relating To Suppositoriesmentioning
confidence: 99%
“…The development of the transmucosal tablet has been shown to be an advance in the delivery of fentanyl. This dosage form was designed to encourage retention of the active substance with the mucosa, so as to increase contact time at the absorption site and avoid the potential intraindividual and interindividual variability resulting from swallowing 25. Onset of action is rapid (8–11 minutes after administration), with available preparations showing dose proportionality 26.…”
Section: Approaches To Breakthrough Painmentioning
confidence: 99%